Thermal Preferences And Critical Temperatures Of Invasive Lionfish - Kerstetter, David; Barker, Benjamin (NSUWorks, 2014)
The Indo-Pacific lionfish (red lionfish Pterios miles and devil firefish P. volitans complex) is a recent invasive species to the western North Atlantic. It has already spread from the initial introduction in South Florida throughout the Greater Caribbean, the Gulf of Mexico, and northward seasonally to New England. In part because of reductions in the populations of native apex predators (e.g., groupers) in reef ecosystems, lionfish have encompassed many of the empty ecological niches. Recent observations suggest that predation is now resulting in depauperate reef fauna where lionfish are firmly established. However, very little is known about either the thermal preferences of lionfish or their thermal tolerance (defined as critical thermal maximum (CTMax) and minimum (CTMin)). Observations of lionfish in the wild at these broad geographic ranges suggests that the complex has a high thermal tolerance range, which is unusual for a tropical species. However, the main dispersal mechanism for lionfish from warm-water southern areas to colder northern areas is through passive transport of the juveniles by longshore and Gulf Stream currents and eddies. Most fishes have narrower thermal tolerance ranges as juveniles, the life-history stage for lionfish individuals facing low overwintering temperatures in northern areas. This proposal would address the missing thermal element to lionfish management efforts by determining the following parameters: thermal preferences and the CTMax/CTMin thermal tolerance levels. These would be evaluated using a well-established "shuttlebox" system that allows the individual fish to select preferred temperatures. Specifically, this proposed work would address these questions using lionfish acclimated to three thermal regimes: 10 °C,20 °C, and 30 °C, simulating the New England, Floridian, and southern Caribbean waters respectively. These three values would allow the further description of lionfish thermal response through the development of critical thermal tolerance polygons.